Inpatients versus outpatients with advanced non-small cell lung cancer: Characteristics and outcomes. (2019) - Gotfrit, Joanna; Jonker, Caleb; Zhang, Tinghua; Goss, Glenwood; Nicholas, Garth; Laurie, Scott; Wheatley-Price, Paul
Highlights: Inpatients represent an important minority of patients presenting to medical oncologists. Patients presenting to medical oncologists through the inpatient department are less likely to receive systemic therapy than their outpatient counterparts, but those who receive systemic therapy are more likely to respond. We must develop tools to identify inpatients who would most benefit from receiving systemic therapy. A bstract: Background: Most newly diagnosed advanced NSCLC patients have an initial medical oncology consult as an outpatient. Sometimes, the initial consult occurs as an inpatient. We explored differences among NSCLC patients presenting to medical oncology while hospitalized versus as outpatients. Methods: With ethics approval, we performed a retrospective analysis of all stage IIIB and IV NSCLC patients at our institution consulted by medical oncology between 2009 and 2012. The primary analysis is descriptive, exploring differences in baseline characteristics, treatment choices, and overall survival (OS). Results: In total, 637 patients were included: 123 inpatients and 514 outpatients. Among outpatients, 55% received systemic therapy compared to 21% of inpatients. Among treated patients, inpatients were likely to be younger (81% vs 70% <70 years, p = 0.04), have PS 3–4 (38% vs 5%, p <0.001), have ≥5% weight loss (54% vs 42%, p = 0.01), anemia (19% vs 4%, p = 0.001), leukocytosis (38% vs 32%, p = 0.001), thrombocytosis (27 vs 23%, p = 0.001), renal dysfunction (12% vs 5%, p = 0.01) and more rapid onset of symptoms (27% vs 6% for <2 weeks, 35% vs 11% for 2–6 weeks; p <0.001). Inpatients who received systemic therapy were more likely to have a complete or partial response (42% vs 26%, p = 0.007), however had a shorter median OS than treated outpatients (8.4 vs 10.5 months, p = 0.003). Conclusions: Patients initially consulted by medical oncologists while hospitalized were more unwell and fewer received systemic therapy. However, if treated, they had higher response rates than outpatients and reasonable OS. Systemic therapy can be considered in hospitalized advanced NSCLC patients. Microabstract: A minority of patients with lung cancer have an initial oncology consultation as an inpatient. We compared the characteristics and outcomes of inpatients with their outpatient counterparts. Inpatients were more unwell at diagnosis and fewer received systemic therapy, but among those who did, they were more likely to respond and their overall survival approached that of the outpatient cohort.